Parental Accountability, School Choice, and the Invisible Hand of the Market. Issue 1 (January 2020) - Potterton, Amanda U.
I introduce the concept of parental accountability by examining how parents understand and cope with what I characterize are pressures fostered by the long-standing public-school choice market in Arizona. Parental accountability refers to the sensemaking, experiences, and consequences that are related to decision-making in a school choice environment, wherein parents' feelings about their child's schooling may be intense, emotionally stressful, malleable, cyclical, and ongoing—not static. I argue that parental accountability is a necessary concept for understanding these reforms. The analysis, based on data collected from a study using ethnographic methods, reveals contradictions between parents' perceptions of their responsibilities to public institutions and pressures to make private choices. Many parents acknowledged that socioeconomic and racial inequities may be exacerbated in some market-based, public-school choice systems. I show how school choice policies and programs can place unique pressure on parents that they experience as a distinct form of accountability.